The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008 IEEE Spoken Language Technology Workshop 2008
DOI: 10.1109/slt.2008.4777886
|View full text |Cite
|
Sign up to set email alerts
|

Recent improvements in BBN's English/Iraqi speech-to-speech translation system

Abstract: We report on recent improvements in our English/Iraqi Arabic speech-to-speech translation system. User interface improvements include a novel parallel approach to user confirmation which makes confirmation cost-free in terms of dialog duration. Automatic speech recognition improvements include the incorporation of state-of-the-art techniques in feature transformation and discriminative training. Machine translation improvements include a novel combination of multiple alignments derived from various pre-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The result showed that the polynomial classifier provided better recognition performance with a faster testing response compared to the DTW recognizer. Additionally, recent developments to English/Iraqi Arabic speech-to-speech translation system were provided in literature (Choi et al, 2008). The system provided wide developments involving machine translation (MT), components dialog manager, user interface (UI), and Arabic Speech Recognition (ASR).…”
Section: Arabic Speech Recognition System Developmentmentioning
confidence: 99%
“…The result showed that the polynomial classifier provided better recognition performance with a faster testing response compared to the DTW recognizer. Additionally, recent developments to English/Iraqi Arabic speech-to-speech translation system were provided in literature (Choi et al, 2008). The system provided wide developments involving machine translation (MT), components dialog manager, user interface (UI), and Arabic Speech Recognition (ASR).…”
Section: Arabic Speech Recognition System Developmentmentioning
confidence: 99%
“…(Alotaibi, 2004) reported achieving highperformance Arabic digits recognition using recurrent networks. (Choi et al, 2008) presented recent improvements to their English/Iraqi Arabic speech-to-speech translation system. The presented system-wide improvements included user interface, dialog manager, ASR, and machine translation components.…”
Section: Literature and Recent Workmentioning
confidence: 99%